Pengaruh body shaming terhadap body image remaja perempuan - Firda Sukma Asmara Ningsih; Hudaniah Hudaniah; Sakinah Nur Rokhmah (Fakultas Psikologi, 2023)
Body shaming is increasingly happening among teenagers. Body shaming is the behavior of negative comments to others or oneself starting from body shape, skin color and condition. Body shaming can lead to body image disturbance, namely negative body image. Researchers suspect that body shaming is one of the causes of a negative body image. Using the quantitative approach, data collected through a body shaming and body image scale with the accidental sampling technique, totalling 355 respondents with the provision that the respondents are teenage girls who have or are currently experiencing body shaming. Data analysis used simple linear regression analysis. The study results showed a sig value of 0.00 <0.05 and an R-value of 0.080, therefore, it was proven that there was an effect of body shaming on adolescent girls' body image, and 100% of respondents had a negative body image. Keywords : Body shaming, body image, teen girl